How Debriefing Strategies Can Improve Student Motivation and Self-Efficacy in Game-Based Learning - Bilgin, Cigdem Uz; Baek, Youngkyun; Park, Hyungsung (SAGE PUBLICATIONS INC, 2015)
Debriefing is an important step in game-based learning environments. Fanning and Gaba defined debriefing as facilitated or guided reflection in the cycle of experiential learning. In the present study, the effect of different debriefing strategies in terms of two factors, grouping (self vs. team) and timing (in-game vs. postgame), was investigated on the motivation and self-efficacy levels of students. In a 2 x 2 analysis of variance design, 62 sixth-grade students were randomly assigned into two debriefing groups: self-debriefing and team debriefing. About half of members in each group performed either one of the two debriefing: in-game debriefing or postgame debriefing. Students in the self-debriefing as well as in the team-briefing group played the game 3 days a week over 9 weeks. As students finished the task, motivation and self-efficacy scales were administered and semistructured interviews were conducted. Findings indicate that students showed higher motivation and self-efficacy scores in the team debriefing than in the self-debriefing. Moreover, the in-game debriefing group outperformed the postgame debriefing group in terms of self-efficacy and motivation levels. Semistructured interviews supported the quantitative results that students benefited more from collaborative debriefing sessions.
Keywords: game-based learning; debriefing; student motivation; self-efficacy; collaborative learning environments; SIMULATION; PERFORMANCE; MANAGEMENT; EDUCATION; Education & Educational Research